ANALISIS TEKNIK SMASH PENUH PEMAIN BULUTANGKIS PEMULA KLUB RAJAWALI - Setyawan, Aditya; Septianingrum, Kartika; Wahyudi, Arief Nur (Dharmas Journal of Sport, 2024)
The research aims to determine the full smash technique of badminton players at the Rajawali club. The research design used is quantitative descriptive, the method used is survey. This research is to describe the badminton full smash shot at the Rajawali badminton club. In this study, using initial observations, the population studied was 25 people. 25 researchers only took a sample of 10 people aged 13 to 15 years to be used as research samples. This sampling technique is purposive sampling, the characteristics of the sample used are willing to be a research sample, badminton players for the Rajawali club, aged 13 - 15 years, minimum of 6 months of training. The research instrument used in this research is data collection by means of individual, observed and assessed. In this research, the judge must be a truly competent person who is a professional in his field. Data collection techniques in this research are tests and documentation. In this research, the collected data is processed using statistical analysis, namely Validity Test, Objectivity Test, Hypothesis Test. The instrument test in this research is the instrument validity test, objectivity. Based on the conclusions carried out by the research, the results of the Full Smash technical analysis assessment of the Rajawali Walikukun club badminton players are in the poor category with a percentage of 0%, the adequate category is 0%, the good category is 0% and the very good category is 100%. Based on the average score, namely 11.6, the results of the full smash technique analysis assessment of the Rajawali Walikukun club badminton players are in the very good category.